Tren Konsumsi Beras dan Implikasinya terhadap Ketahanan Pangan di Ponorogo Tahun 2021–2023 - Prasetyo, Mohammad Andre; Fadila, Anis (Journal of Economics and Social Sciences (JESS), 2024)
Introduction/Main Objectives: Rice consumption in Indonesia reflects the socio-economic dynamics of society and serves as an important indicator for assessing national food security, including at the local level. This article aims to analyze the Trends in Rice Consumption and Its Implications for Food Security in Ponorogo from 2021 to 2023. Research Methods: The study uses secondary data obtained from the Central Statistics Agency and other relevant sources, such as local government reports. The analysis is conducted using a descriptive quantitative approach, involving the evaluation of consumption trends, prices, and rice demand elasticity. Finding/Results: The results show that per capita rice consumption in Ponorogo has declined from 1.436 kg/week (2021) to 1.390 kg/week (2023). Key factors include food diversification, increased awareness of healthy eating habits, and changes in purchasing power. Rice demand is inelastic to price increases, indicating that rice remains an essential and irreplaceable staple. Conclusion: The conclusion of this study is that the decline in rice consumption reflects a shift in consumer food preferences towards more diverse options. The implication of these findings is the need for an effective food diversification strategy to maintain food security. Government policies should consider local socio-economic dynamics when designing food programs.